PENGARUH KUALITAS WEB DIRASAKAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI TERHADAP SIKAP BERBELANJA ONLINE PADA PENGGUNA PORTAL LAZADA.CO.ID KOTA BANDA ACEH - Muhammad Farizs Akbar, Iskandarsyah Madjid (Departemen Manajemen, 2017)
The purpose of this study is to determine the influence of perceived web quality towards online shopping attitudes, with trust as a mediating variable. The samples used in this study were 200 respondents who have accessed and made purchases on Lazada.co.id website. The sampling technique used was Purposive Sampling. Hierarchical Linear Modeling (HLM) method was used as a method of analysis to determine the effect of the variables involved. The results of this study showed that the perceived web quality had a significant effect toward online shopping attitudes. In addition, the results showed that the trust variable partially mediated the influence of the perceived web quality toward online shopping attitudes. The better the owned perceived web quality, the better the perception of the trust, thus the higher the customer’s online shopping would be. Keywords: Perceived Web Quality, Online shopping attitudes, Trust.